The Use of Discovery Learning with Hands on Activity to Mathematical Literacy - Abdullah Abdullah (International Conference on Science, Education, and Technology, 2023)
The background of this research is caused by the problem of low mathematical literacy ability which causes some students to be unable to solve mathematical contextual problems. The teacher centered learning process does not provide opportunities for students to develop their ideas properly so that students find it difficult to understand concepts correctly. Discovery learning is student centered learning so that students can build their ideas and discover concepts through their mental processes. Hands on activity is a learning media that supports student learning activities. The purpose of this study was to determine the effectiveness of discovery learning with hands on activity on mathematical literacy. This study uses a mixed methods. The research data was obtained through tests of students mathematical literacy, interviews and observation. The research sample consisted of 66 students of class X semester 1 of SMAIT Nurul Islam Tengaran. Quantitative data analysis using descriptive and inferential statistics. Qualitative research subjects were obtained from students who had the highest ranking in the previous class. So that the two highest ranking subjects were chosen, namely S1 and S2. The gain test obtained a significance of 0.000 <0.05, this indicates that there is an increase in mathematical literacy in the experimental class which is higher than the control class. The subject of S1 is able to master the 5 indicators of mathematical literacy very well. While S2 is able to master the 4 indicators of mathematical literacy well. Through discovery learning with hands on activity students can improve their mathematical literacy ability.